The Mapping of Predicted Triplex DNA:RNA in the Drosophila Genome Reveals a Prominent Location in Development- and Morphogenesis-Related Genes. Issue 7 (1st July 2017) - Pasquier, Claude; Agnel, Sandra; Robichon, Alain
Abstract: Double-stranded DNA is able to form triple-helical structures by accommodating a third nucleotide strand. A nucleic acid triplex occurs according to Hoogsteen rules that predict the stability and affinity of the third strand bound to the Watson–Crick duplex. The "triplex-forming oligonucleotide" (TFO) can be a short sequence of RNA that binds to the major groove of the targeted duplex only when this duplex presents a sequence of purine or pyrimidine bases in one of the DNA strands. Many nuclear proteins are known to bind triplex DNA or DNA:RNA, but their biological functions are unexplored. We identified sequences that are capable of engaging as the "triplex-forming oligonucleotide" in both the pre-lncRNA and pre-mRNA collections of Drosophila melanogaster . These motifs were matched against the Drosophila genome in order to identify putative sequences of triplex formation in intergenic regions, promoters, and introns/exons. Most of the identified TFOs appear to be located in the intronic region of the analyzed genes. Computational prediction of the most targeted genes by TFOs originating from pre-lncRNAs and pre-mRNAs revealed that they are restrictively associated with development- and morphogenesis-related gene networks. The refined analysis by Gene Ontology enrichment demonstrates that some individual TFOs present genome-wide scale matches that are located in numerous genes and regulatory sequences. The triplex DNA:RNA computational mapping at the genome-wide scale suggests broad interference in the regulatory process of the gene networks orchestrated by TFO RNAs acting in association simultaneously at multiple sites.